Differences between 48 and 72-hour intervals on match load and subsequent recovery: a report from the Brazilian under-20 national football team - Wilke, Carolina Franco; Coimbra, Cândido Celso; Drummond, Filipe R.; Drummond, Lucas Rios; Campos, Helton Oliveira; Kanope, Tane; Ramos, Guilherme Passos (Frontiers in Sports and Active Living, 2024)
Purpose: To compare football players' external and internal load and subsequent recovery from international tournament matches interspersed by 48h vs 72h. Methods: 18 male soccer players from the Brazilian National Team competing in the 2019 South American Uunder-20Championship participated in the study. Match load was quantified using GPS variables and rating of perceived exertion (1). Additionally, before and after 13-15h from each match, players answered to number of hours and quality of sleep, recovery state and muscle soreness (0-10) and provided a blood sample for CK creatine kinase and reactive C-protein PCR analysis.Values from all variables were compared between matches played with 48h interval (matches 1 -4) and 72h interval (matches 5 -8). Results: No significant differences were observed on performance or perceptual parameters amongst matches (p = 0.136 to 0.953). However, CK